2007
DOI: 10.1002/ajmg.a.31615
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 18: Fetal ultrasound findings at different gestational ages

Abstract: The aim of this article is evaluate the sonograhic findings in fetuses with trisomy 18 at different gestational ages. The cases were recruited from pregnant women, who underwent to prenatal diagnosis in the period from October 1995 to September 2006. Seventy-one fetuses with trisomy 18 were diagnosed. On review of the sonograms the majority of these cases had ultrasound anomalies (sensitivity of 91.5%). The most frequent anomalies were abnormalities of extremities (40.8%) and fetal growth restriction (35.2%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 18 publications
6
20
0
Order By: Relevance
“…One or more sonographic anomalies are detected in over 90% of fetuses; two or more abnormalities are present in 55% of cases [38]. The prenatal sonographic pattern of trisomy 18 is characterized by growth retardation, polyhydramnios, “strawberry-shaped” cranium (brachycephaly and narrow frontal cranium), choroid plexus cyst, overlapping of hands fingers (second and fifth on third and fourth respectively), congenital heart defects, omphalocele, and single umbilical artery [30,35-39].…”
Section: Antenatal Diagnosismentioning
confidence: 99%
“…One or more sonographic anomalies are detected in over 90% of fetuses; two or more abnormalities are present in 55% of cases [38]. The prenatal sonographic pattern of trisomy 18 is characterized by growth retardation, polyhydramnios, “strawberry-shaped” cranium (brachycephaly and narrow frontal cranium), choroid plexus cyst, overlapping of hands fingers (second and fifth on third and fourth respectively), congenital heart defects, omphalocele, and single umbilical artery [30,35-39].…”
Section: Antenatal Diagnosismentioning
confidence: 99%
“…The prevalence of IUGR increased to 89% after 24 weeks. Viora et al 21 found growth restriction prevalence rates of 14% before 16 weeks and 55% after this time in fetuses with trisomy 18. This series included 71 fetuses with trisomy 18, but only 20 were at 14 to 21 weeks' gestation, and IUGR was defined as an AC below the 10th percentile.…”
Section: Discussionmentioning
confidence: 97%
“…4 Other conditions to rule out are those characterized by upper limb mesomelic hypoplasia such as Roberts syndrome and trisomy 18. 10,11 In the first case, the upper limb hypoplasia can be so severe that it results in phocomelia, while Edwards syndrome is characterized by other sonographic findings such as micrognathia, ear and cardiac anomalies, overlapping findings, rocker-bottom feet, dysplastic kidneys, and cerebral malformations. Fetal valproate syndrome, which is characterized by transverse and not longitudinal deficiency, was easily excluded because of a negative history of treatment with valproic acid.…”
Section: Discussionmentioning
confidence: 99%